No Comment?! The Drivers of Reactions to Online Posts in Professional Groups. Issue 1 (August 2016) - Rooderkerk, Robert P.; Pauwels, Koen H.
Social media has moved beyond personal friendships to professional interactions in high-knowledge industries. In particular, online discussion forums are sponsored by firms aiming to position themselves as thought-leaders, to gain more insight in their customer base and to generate sales leads. However, while firms can seed discussion by posts, they depend on the forum members to continue the discussion in the form of reactions to these posts. The goal of the current study is to investigate what features and characteristics drive the number of comments that a post receives on an online discussion forum. The empirical setting involves a global manufacturer connecting with health care professionals through a LinkedIn discussion forum. We project that (i) content characteristics, (ii) post characteristics, (iii) author characteristics, and (iv) timing characteristics jointly determine the number of comments a post receives. We show that the readability of the post, the controversiality of the content and the status of the post author have the highest elasticity on the number of comments. These results provide valuable insights for firms on how to build and maintain an attractive online forum through ongoing discussions.